2018
DOI: 10.1021/acsbiomaterials.8b00313
|View full text |Cite
|
Sign up to set email alerts
|

Initial Priming on Soft Substrates Enhances Subsequent Topography-Induced Neuronal Differentiation in ESCs but Not in MSCs

Abstract: Differentiation of stem cells into neurogenic lineage is of great interest for treatment of neurodegenerative diseases. While the role of chemical cues in regulating stem cell fate is well appreciated, the identification of physical cues has revolutionized the field of tissue engineering leading to development of scaffolds encoding one or more physical cues for inducing stem cell differentiation. In this study, using human mesenchymal stem cells (hMSCs) and mouse embryonic stem cells (mESCs), we have tested if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…With the priming step, neuronal differentiation was improved in mESC, and the authors suggested that soft substrates are essential for inducing topography-mediated neuronal differentiation in mESCs. 204 The observations were in agreement with earlier studies to show that cytoskeletal contractility is essential for topography-sensing and topography-induced neuronal differentiation of human ESCs. 205 Undifferentiated pluripotent stem cells including hESCs 205 and mESCs 206 have lower acto-myosin contractility compared to differentiated cells, while the acto-myosin contractility increased during differentiation process.…”
Section: Surface Topography Affect Cell Responses On Hydrogelsupporting
confidence: 92%
“…With the priming step, neuronal differentiation was improved in mESC, and the authors suggested that soft substrates are essential for inducing topography-mediated neuronal differentiation in mESCs. 204 The observations were in agreement with earlier studies to show that cytoskeletal contractility is essential for topography-sensing and topography-induced neuronal differentiation of human ESCs. 205 Undifferentiated pluripotent stem cells including hESCs 205 and mESCs 206 have lower acto-myosin contractility compared to differentiated cells, while the acto-myosin contractility increased during differentiation process.…”
Section: Surface Topography Affect Cell Responses On Hydrogelsupporting
confidence: 92%
“…Since the piezoelectric material generated an electric potential by converting mechanical forces such as cell movement and traction, rat bone marrow-derived MSCs were directly seeded onto the substrates without further electrical stimulation. Based on the data collected from the study, when 200 [55] published by American Chemical Society 2019, reproduced with permission from [56] published by Elsevier 2020) ◂ and 500 nm patterned polyvinyl chloride (PVC) was used as non-electrical control, nanotopography was sufficient to promote the cellular adhesion of the stem cells. However, only the combination with PVDF could greatly enhance the neuron-like differentiation of the MSCs at the 200 nm pattern.…”
Section: Topography-guided Mesenchymal Stem Cell Lineage Reprogrammingmentioning
confidence: 99%
“…However, after priming mESCs on a softer flat gel (1 kPa), their viability and neural differentiation were enhanced, whereas hMSCs did not respond to such priming. [97] To mimic the in vivo physical properties and/or to understand more delicate details of stem cell differentiation, recent studies have been investigating how the change/gradient of stiffness can affect stem cell differentiation and migration. Limitations exist, however, in producing hydrogels with stiffness gradients, such as cost, complex techniques, small stiffness ranges, poor biocompatibility, and lack of reproducibility.…”
Section: D Hydrogel Modelsmentioning
confidence: 99%
“…studied the collective effects of substrate stiffness and topography on neural differentiation of hMSCs and mESCs. [ 97 ] Unlike hMSCs that expressed neural markers on 5 kPa gels with grating topography, mESCs did not differentiate. However, after priming mESCs on a softer flat gel (1 kPa), their viability and neural differentiation were enhanced, whereas hMSCs did not respond to such priming.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation